Sensemaking through cue utilisation in disaster recovery project management. Issue 5 (July 2017) - Gacasan, Eva Marie P.; Wiggins, Mark W.
Abstract: This study examined the role of cue utilisation as a basis for sensemaking in disaster recovery project management. Sensemaking is a critical skill that involves organising and prioritising information to achieve an accurate representation of project situations. A mixed between-within groups design was used to test three groups of participants with different levels of project management experience in the context of disaster recovery. A total of 68 participants completed a situation judgment test that incorporated assessments of four elements of cue utilisation related to disaster recovery project management: cue identification, cue precision, cue discrimination, and cue prioritisation. Statistically significant differences in performance were evident between naïve and non-naïve groups in cue identification, cue precision and cue prioritisation. The results confirm the role of cue utilisation in the context of disaster recovery project management and provide the basis for an assessment tool that could be deployed in practice. Highlights: Established the role of cue utilisation in disaster recovery sensemaking through a comparative assessment Different levels of operational experience were associated with differences in cue utilisation The evaluation of cue utilisation performance is a basis for training and assessment of practitioners' diagnostic skills